DOI: 10.11606/t.6.2018.tde-04012018-165436
|View full text |Cite
|
Sign up to set email alerts
|

Análise do ciclo de política do Programa Mais Médicos no Brasil: cooperação Cuba Brasil e seus efeitos para o trabalho médico

Abstract: The education and provision of health professionals are the main strategies to increase capacity and respond to health systems' needs among countries worldwide. Recently, the Brazilian government passed a law to create a national program, called the More Doctors Program, to improve the capacity to respond to the demand for doctors in underserved areas. The law was designed with three main axes: provision, education and infrastructure. The first, provision, would increase the provision of medical doctors throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Furthermore, we had to analyze the role of entrepreneurs who led the PMM formulation process to assess its decisive moments and fundamental characteristics. Studies, such as Gomes (2016) and Paula (2017), found these individuals as protagonists in the PMM implementation but ignored the analysis of their role in its formulation. Strategically positioned in the Ministry of Health, MEC, and the National Congress, since the beginning of Dilma's Government, they acted strategically to create and seize "windows of opportunity," aiming to change an institutional arrangement which had been stable until then (Pinto;Côrtes, 2021a).…”
Section: Discussion and Final Considerationsmentioning
confidence: 99%
“…Furthermore, we had to analyze the role of entrepreneurs who led the PMM formulation process to assess its decisive moments and fundamental characteristics. Studies, such as Gomes (2016) and Paula (2017), found these individuals as protagonists in the PMM implementation but ignored the analysis of their role in its formulation. Strategically positioned in the Ministry of Health, MEC, and the National Congress, since the beginning of Dilma's Government, they acted strategically to create and seize "windows of opportunity," aiming to change an institutional arrangement which had been stable until then (Pinto;Côrtes, 2021a).…”
Section: Discussion and Final Considerationsmentioning
confidence: 99%
“…Finally, this pedagogical relationship enables a cultural, technical and scientific exchange that brings innovation and a "mosaic of possibilities" to public health policies and medical education in the country 14 . Some professionals, for example, have experience in management, teaching and research, and could contribute with scientific production in the area, with indigenous health protocols or supervising interns from Rural Residency 15 , not being restricted to healthcare in the villages.…”
Section: (S7)mentioning
confidence: 99%
“…Supervisors' motivation varies according to the doctor's perception of the work's nature. It can be humanitarian, mainly based in solidarity and internationalist vocation to some Cubans 14,26 ; temporary, mainly among Brazilians who want to work in medical residency or between foreigners and Brazilians graduated overseas who want to revalidate their diploma; or realistic, as real agents in a public health system under construction.…”
Section: Embracement Makes Professionals Feel Supported Professionalmentioning
confidence: 99%